THE ROLE OF CULTURE IN RAISING MORAL AND YOUTH - D .Q.Oxunova (TADQIQOTLAR.UZ, 2023)
Spiritual and moral education of students is a priority task of the modern education system and is an important component of the social order for education. Education plays an important role in the spiritual and moral strengthening of our society. Society is able to set and solve large-scale national tasks only when it has a system of general moral guidelines. They have such interesting places where respect is shown to their mother tongue, their own culture and their own cultural values, the memory of their ancestors, every page of the national history.